Study of Hemoglobin Determination in Pregnant Cows at Beni Hesar Dairy Farm - Stanikzai, Nasrin; Hamed, Asadullah (Journal of Natural Sciences – Kabul University, 2022)
Pregnancy is a stage during which animals face various challenges. One of these challenges is anemia during pregnancy. The amount of hemoglobin per 100 ml of blood is normally between 8-15 grams. Hemoglobin acts as a pigment for the respiratory system and also functions as an internal buffer system in the blood. The essential materials used to determine hemoglobin in this study are pregnant cows and blood samples. The cows were divided into three groups based on their age. The mean levels of hemoglobin in the three groups showed variable results based on the age of the animal. These results indicated a lower decrease in hemoglobin levels in the younger cows, but the decline was more significant in older cows. Therefore, we conclude that the decrease in hemoglobin levels in pregnant cows is directly related to the age of the animal.